Infectious diseases - Spears, David (Oxford : Science Pictures for Oxford University Press, 1994)
This video presents the major categories of disease-causing microorganism in man such as viruses, bacteria, eukaryotic parasites. For each category the main pathogenic mechanisms are oulined, and the principal immunological defencesystems deployed (and the invader's countermeasures) are described
Copy available in DVD format
Keywords: Communicable diseases; Infection